Biological Water Quality Indices Performance Based on Aquatic Insects in Recreational Rivers - Ahmad Hadri Jumaat; Suhaila Abdul Hamid (Tropical Life Sciences Research, 2021)
Abundance and distribution of aquatic insects respecting to several water chemical parameters from six rivers were studied in order to determine the performance of biological index in monitoring the water quality. A total of 960 individuals of aquatic insects from nine orders were recorded using kick and drag sampling techniques. Lubok Semilang had the greatest number of aquatic insect with 250 individuals, followed by Telaga Tujuh (181 individuals) and Sungai Durian Perangin (171 individuals). EPT (Ephemeroptera, Plecoptera and Trichoptera) order were the most dominant order recorded in all six rivers. Lata Kekabu had more diverse and richer aquatic insect assemblages based on ecological indices compared to the other five rivers. In order to evaluate the water quality of recreational rivers in Malaysia, Family Biotic Index (FBI), Malaysian Family Biotic Index (MFBI) and Biological Monitoring Working Party (BMWP) were used and compared with Water Quality Index to determine the water quality at the study areas. Results demonstrated that the biotic indices were more sensitive towards changes in water parameters than the WQI. Among all the biological indices, Malaysian Family Biotic Index (MFBI) was the most suitable index to be adopted in Malaysian river water assessment as it is more reliable in assessing the status of water quality.